Analisis Kualitas Pelayanan E-KTP di Kecamatan Tallo Kota Makassar - Ridwan, Muhammad Fadhil; Syahida, Raina Atha; Kawadisi, Mayday Yeti (Institut Pemerintahan Dalam Negeri Kampus Sulawesi Selatan, 2023)
This research aims to analyze the quality of E-KTP services in Tallo District, Makassar City. The new public service paradigm presented, the author believes that all of this emphasizes citizen participation in formulating public service programs that support the needs of citizens, have equal rights, provide space for public participation and transparency of service providers in dealing with citizens. state, accountability in accordance with programs, norms and implementation carried out by bureaucratic institutions so far. Through qualitative research methods, the results show that E-KTP services in Tallo District show that the quality of service is still less than optimal. This is due to the fact that the number of employees in the service department is still very insufficient in serving the community, starting from a shortage of employees and several employees who lack discipline. When the break time is over, employees are found not to be in the Tallo District office, which causes service employees in the Tallo District office to suffer. The workload has increased due to the limited number of employees available to serve the community, so that these employees experience excessive stress in checking files and inputting community data in the process of making E-KTPs in Tallo District, Makassar City.